Transformasi Administrasi Kesehatan Masyarakat Dalam Penguatan Tata Kelola Pelayanan Kesehatan Primer Di Era Digital Tahun 2025: Suatu Tinjauan Literatur - Nurcholisah Fitra; Syafrina Ulfah (STIKES Columbia Asia Medan, 2025)
Public health administration plays a strategic role in strengthening primary health care governance amid increasingly complex health system challenges. This study aimed to synthesize recent evidence on the development, challenges, and implications of public health administration during the period 2020–2025. A literature review with a systematic approach was conducted by analyzing peer-reviewed articles retrieved from major scientific databases and selected through a PRISMA 2020 flow process. The findings indicate that effective public health administration—characterized by strong governance, adaptive leadership, and the integration of digital health information systems—contributes to improved performance of primary health care services in terms of service quality, efficiency, and sustainability. However, the review also reveals persistent gaps, particularly the limited empirical evidence examining causal relationships between administrative capacity and health service performance, as well as challenges related to human resource readiness and data governance in digital transformation. These findings highlight the need to strengthen administrative capacity, leadership competencies, and integrated information systems to support resilient primary health care. The study provides theoretical and practical implications for policymakers, health managers, and researchers in advancing public health administration toward more effective and sustainable health systems.